An Isolated DC-DC Converter for 800 V Electric Vehicle With Wide Soft-Switching Range and Low Voltage Stress on Power Switches - van-Cuong Bui; Khai M. Nguyen; Duy T. Duong; Dai-van Vo; Young-Cheol Lim; Joon-Ho Choi (IEEE Access)
This paper proposes an isolated DC-DC converter to cope with 800 V input voltage and 48 V output voltage conditions of the auxiliary power module in the next generation 800 V electric vehicles. On the primary side, a split-capacitor structure and a series capacitor are utilized while on the secondary side, a current doubler rectifier is designed, which repeats a part of the primary structure. Compared with existing isolated converters, the proposed converter has attractive characteristics: 1) a double step-down ratio; 2) the voltage stress on all primary switches and primary transformer are reduced to half of the input voltage; 3) the power switches have soft-switching capability by ZVS characteristic in the primary side, ZV-ZCS in secondary side; 4) the soft-switching range is wide, which maintained even at light-load conditions. 5) allow reuse conventional devices of 400 V system in the updated 800 V system. These characteristics are achieved with a simple control strategy by the pulse width modulation method for switches on the primary side and only repeating primary gating signals for switches on the secondary side. In this paper, the operation and performance of the proposed converter are presented. Besides, an experiment at 800 V input, 48 V–1.2 kW output is also completed to validate the operation and effectiveness of the proposed converter.